Dívida, comportamento responsável em relação ao crédito e cadastro positivo - Carvalho, Caio Henrique Decicco de (2021)
Through the theoretical lens of the Theory of Planned Behavior (TPB), the research aims to identify the determinants for consumers to adopt responsible credit behavior and avoid risky behaviors that lead to indebtedness. We found that knowledge about Positive Credit Report has positive effects on attitude and intention to adopt responsible credit behavior. Also, friends’ social norms and self-efficacy have significant effects over intention and risky credit behavior. Pro-consumption attitude and self-efficacy, by the other side, have not shown significant effect over intention to adopt responsible credit behavior, despite path coefficients confirming negative effects, in agreement with previous literature. We found that consumers that most check their credit scores, and have more knowledge about Positive Credit Report, are the indebted ones. This finding suggests opportunities to spread Positive Credit Report as a financial education tool, since consumers that are not indebted, and have low credit risky behavior, do not check their credit scores, and reported less knowledge about Positive Credit Report. This research has two major contributions to indebtedness study using TPB models. The first one is the investigation of friends’ social norms on adult life, and the second one is an adaptation of Positive Credit Report as a financial knowledge variable. The findings suggests that behavioral variables can explain risky credit behaviors. Theses variables could complement credit analysis in Brazil.